(untitled) (Palíndromo, 2025)
A conversation between two South American travestis about the travesti power to reinvent languages and futures. In times of collapse, we can only exist as birds, because we don’t ask permission to be, because we are invention and urgency. We inherit the rebellion of those who came before, honor their memories, and plant seeds for those yet to come. We create mirrors, multiply words, forge new paths, and that’s why we’re dangerous. We’re dangerous because we refuse the world as it’s given to us, writing new possibilities with our bodies, as maps of resistance, as living archives that dismantle this world’s certainties. We write, sing, and dance like dangerous birds who dream and shout the desire to keep dreaming.